Wage bargaining and the (dynamic) mincer equation - Corrado Andini (Institute for the Study of Labor (IZA), 2008)
This paper shows that, if observed earnings are the result of employer-employee wage bargaining, under a set of specific assumptions, the standard static Mincer equation can be thought as a particular case of a dynamic wage equation. Particularly, we argue that the standard static Mincer equation is implicitly based on the hypothesis that the employee has full bargaining power, and provide (further) empirical evidence against this hypothesis.
urn:nbn:de:101:1-20081127512
Keywords: I21; 330; Mincer equation; return to schooling; wage bargaining; Bildungsertrag; Lohnverhandlungen; Schätzung; Spanien